2023
DOI: 10.1039/d3sm01214j
|View full text |Cite
|
Sign up to set email alerts
|

Selecting active matter according to motility in an acoustofluidic setup: self-propelled particles and sperm cells

Vyacheslav R. Misko,
Larysa Baraban,
Denys Makarov
et al.

Abstract: Selecting sperm cells or self-propelled Janus particles according to their motility in an acoustofluidic setup: the acoustic trap focuses cells/particles near the channel centerline, and motile species escape the trap and can be collected separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It was shown that the effect of escape was observed in both stationary conditions, i.e., in the absence of external flows and when an externally driven fluid flow along the channel was applied. This selective escape can be useful for various applications where one needs to select active species from passive, for example, motile sperm cells from immotile, as was recently demonstrated elsewhere [29]. In this work, we focused on the escape of Janus particles and analyzed the distributions of active versus passive particles across the channel width.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It was shown that the effect of escape was observed in both stationary conditions, i.e., in the absence of external flows and when an externally driven fluid flow along the channel was applied. This selective escape can be useful for various applications where one needs to select active species from passive, for example, motile sperm cells from immotile, as was recently demonstrated elsewhere [29]. In this work, we focused on the escape of Janus particles and analyzed the distributions of active versus passive particles across the channel width.…”
Section: Discussionmentioning
confidence: 91%
“…Note that passive Brownian particles, which execute random walk, are characterized by zero persistence length. The motility of self-propelled particles is the measure of their ability to escape from an acoustic trap, the same as natural swimmers like sperm cells [29].…”
Section: Self-propelled Motion Of Janus Particles and Motilitymentioning
confidence: 99%
See 1 more Smart Citation